Recognising the barriers to securing affordable housing through the land use planning system in Sub-Saharan Africa: A perspective from Ghana. (September 2018) - Agyemang, Felix SK; Morrison, Nicky
Housing low-income households is a daunting task for policy makers across the Global South, and especially for those in Africa where past attempts to deliver State-funded affordable housing projects yielded minimal results. Presenting Ghana as a case study, the purpose of this article is to consider the rationale for and barriers to securing affordable housing through the planning system, situated within an African context. The key factors that would inhibit effective policy implementation include, on the one hand, a lack of central government commitment, weak enforcement of planning regulations and low capacity of local planning authorities, and, on the other hand, the dominance of customary land ownership and the informal nature of housing delivery. That notwithstanding, undertaking a mapping exercise of large-scale formal residential developments built across Greater Accra in recent years, the article suggests that there is an opportunity cost in not attempting to extract some form of economic rent from the private sector. By having an already established nationalised development rights system alongside a rising formal real estate market, there is in effect scope for introducing planning obligations in the longer term. Whilst by necessity, it takes time to fully establish and enforce this form of land value capture legislation; nonetheless, if the principles can be established, transferable lessons exist across Africa and the Global South.